Global navigation satellite systems` receivers in mountain running: the elevation problem - Szot, T.; Sontowski, M. (Sports Engineering, 2024)
The popularity of sports and recreational receivers of the global navigation satellite systems is steadily increasing and provides athletes, coaches, and scientists with a wealth of information on movement occurring both horizontally and vertically. Under mountainous conditions, considering the effort put in by the athlete as well as their safety, the elevation parameter appears to be particularly relevant. The aim of the study was to propose a methodology for assessing sports receivers in terms of their determination of the elevation component based on digital elevation models while paying attention to the appropriate measures for testing these devices. The methodology was applied for wrist-worn global navigation satellite systems` receivers used by the participants of an uphill running event. In terms of elevation determination, the most accurate three receivers (same model) were those supported by the barometric altimeter, in which the Root Mean Square result obtained ranged from 3.6 to 4.1 m. The majority of receivers underestimated the total elevation gain, the mean value of which was -3.8%, which does not appear to be affected by the reception of two global navigation satellite systems or the use of a barometric altimeter. The error characteristics were common within the group of receivers of a particular manufacturer.